ANALISIS EFISIENSI PENGGUNAAN MODAL KERJA PADA PT. BANK MANDIRI SYARIAH (PERSERO) TBK 2012-2016 - Herlina, Tati; ., Destiana (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2021)
Data analysis techniques used is descriptive. Based on the results of the study indicate that the liquidity ratio of the company PT. Bank Mandiri Syariah (Persero) Tbk has a high value of more than 100%, meaning that the company PT. Bank Mandiri Syariah (Persero) Tbk is able to fulfill obligations in a timely manner and the company PT. Bank Mandiri Syariah (Persero) Tbk can be said in the company's activities is not financed by debt Solvency ratios measured through capital Adequacy ratio, debit to equity ratio and debit to asset ratio indicate that the company is able to manage its capital to reduce the level of corporate bankruptcy in the future. The profitability ratio of a company that has a value that is not high enough is measured through the ratio of return on assets, return on equity and net profit margin. Bank Mandiri Syariah (Persero) Tbk.